Participant Experiences and Views of Odor and PrePex Device Removal Pain in a VMMC Pilot Study in Botswana. (1st June 2016) - Musiige, Adrian M.; Ashengo, Tigistu A.; Stolarsky, Galina; Dialwa, Rosinah T.; Manda, Robert; Ntsuape, Conrad O.; Mafeni, Jerome; Busang, Lesego; Curran, Kelly; Motlhoiwa, Kenanao; Mwangemi, Frank J.; Lukobo-Durrell, Mainza; et al.
Abstract : Objective: To assess participant experiences and perceptions of removal pain and odor associated with the PrePex device procedure. Methods: We analyzed data from a PrePex device pilot implementation study of 802 male participants aged 18–49 years at 2 clinics in Botswana, 2013. Study staff administered survey questions on device-related odor and assessed pain using visual analog scale scores categorized as no pain (0), mild (1–4), moderate (5–7), or severe pain (8–10). Results: Mean participant age was 27.7 (range = 18–48) years. Of the 802 participants, 751 (94%) reported to have noticed an unusual or unpleasant odor while wearing the device. Of these, 193 (26%) participants tried something to combat the odor. A total of 84 (10%) participants reported no pain, 655 (82%) mild pain, 48 (6%) moderate pain, and 15 (2%) severe pain at 2 minutes after device removal. Pain reports at 15 minutes after removal were 553 (69%) no pain, 247 (31%) mild pain, and 2 (0.25%) moderate pain, with no report of severe pain at this time point. Of 740 participants interviewed on day 42 after device placement, 678 (92%) were satisfied with the procedure and 681 (92%) would recommend it to another man considering circumcision, including 488 (66%) who would recommend it strongly. Conclusions: An unusual or unpleasant odor while wearing the PrePex device and mild self-limiting pain at device removal were common, but overall, these did neither seem to impair satisfaction nor deter participants from recommending PrePex to others, which could suggest good prospects for uptake of the device in this setting.